Analisis Sistem Penggunaan Aplikasi Keuangan Tingkat Instansi (SAKTI) Dalam Penganggaran Balai Besar Pendidikan Dan Pelatihan Kesejahteraan Sosial - Wildan Said; Reni Yendrawati (Akuntansi, 2023)
The Institution Level Financial Application System (SAKTI) is an application part of the Integrated Financial Management Information System (IFMIS) which must be used by institutions/work units managing funds originating from the APBN. This system is designed to support financial management principles that are more orderly, effective, efficient, economical, transparent, accountable, integrated and performance-based. The aim of this research is to analyze the use of SAKTI in providing convenience in budgeting, obstacles when using SAKTI, and alternative technical methods if there are obstacles when using SAKTI. This type of research is descriptive qualitative with data collection methods by direct observation in the field and collecting additional data and information from credible sources. The results of the research that has been carried out indicate that SAKTI is proven to be able to provide easy access for institutions/work units, although there needs to be a solution to overcome existing obstacles.